Chemical Constituents and Pharmacological Activities of Rabdosia japonica var. glaucocalyx - Bao Xiang, Zhao; Wen Tong, San; Wang, Yun; Lin He, Cong; Hui Li, Xiao (Asian Journal of Chemistry, 2012)
Rabdosia japonica var. glaucocalyx is a widely growing plant in northeast Asia, such as China, Russia, Korea and Japan, which has been used as folk medicine for the treatment of hepatitis, gastricism, mastitis and coughing in China. Recently, it was reported that the Rabdosia japonica var. glaucocalyx has other bioactivities such as antitumor, antioxidation, antiinflammatory and antibacteria. The results of toxicological tests indicated that the Rabdosia japonica var. glaucocalyx is safe to human within the scope of the experimental dose. An attempt has been made to review the chemical constituents and pharmacological activities of Rabdosia japonica var. glaucocalyx.